Restaurant customers' emotional experiences and perceived switching barriers: a full-service restaurant setting - Han, Heesup (Kansas State University, 2007)
This study attempted to develop a multi-item scale that measures restaurant customers' emotional experiences and has desirable reliability and validity, and to examine the relationships among consumption emotions, customer satisfaction, switching barriers, and revisit intention in the full-service restaurant industry. In the process of developing a consumption emotion measurement scale, this study followed Churchill's (1979) paradigm during the early stage and confirmatory factor analytic approach suggested by Gerbing and Anderson (1988) and Anderson and Gerbing's (1988) in the later stage. The scale development process began with a specification of domain of construct, generation of 40 items, and data collection. The collected data were subjected to item refinement (i.e., outlier detection, descriptive and reliability analysis, and exploratory factor analysis). Four underlying dimensions of consumption emotions with 32 refined items were identified from the data. A new sample of data was collected for additional testing (i.e., reliability and validity). A confirmatory factor analysis using the new data indicated that the finalized measure using categorical dimension approach was unidimensional, reliable, and valid. The results of structural equation modeling supported the criterion validity indicating that the finalized measure behaves as expected in relation to additional construct. In study two, a theoretical framework for understanding the relationships among consumption emotions, customer satisfaction, switching barriers, and revisit intention was proposed and tested. A series of modeling comparisons provided a best fit model. A measurement model estimated on the basis of Anderson and Gerbing's (1988) approach tested validity of measures. The results of structural equation modeling using the data from a web-based survey addressed the effect of consumption emotions on satisfaction and revisit intention. The partial/full mediating impact of satisfaction was verified following Baron and Kenny’s (1986) suggested process. The switching barriers, two positive (i.e., preference and relational investment) and two negative (i.e., switching costs and lack of alternatives), that restaurant customers are likely to perceive were identified through the qualitative approach, using the guidelines suggested by Maxwell (2005). The quantitative approach validated the scale applicability. The moderating role of switching barriers in forming revisit intention was verified by testing for metric invariances. Grouping was done by using K-means cluster analysis. Measurement invariance tests supported full metric/partial metric invariances. Structural invariance tests and invariance tests for a hypothesized path provided the evidence of moderating effect of switching barriers. Finally, theoretical and managerial implications of the findings were discussed.
Keywords: Consumption Emotion Scale; Switching Barriers; Customer Satisfaction; Revisit intention; Full-Service Restaurant; Business Administration, General (0310); Business Administration, Management (0454); Business Administration, Marketing (0338)